Development and acceptability of breads added with cocona flour (Solanum sessiliflorum Dunal): impact on the glycemic index (Research, Society and Development, 2022)
The objective of this study was to develop whole wheat bread formulations enriched with cocona flour, in order to analyze its action on the glycemic index in vitro. The development of the breads occurred with the addition of different concentrations of the fruit flour (2,5% and 5%). All the breads were evaluated in their nutritional composition by the food chemical composition tables, and were also submitted to starch digestion and hydrolysis to determine their glycemic index and glycemic load. The coloration of the formulations was evaluated by the CIELab scale, and a sensorial evaluation was made by a nine-point hedonic scale with 112 tasters.  The results showed that the breads elaborated in concentrations of 2,5% (PI 2,5%) and the breads added with 5% of cocona flour (PI 5%) have low fat content and high fiber content (PI 2,5% 7,99 g/100g and PI 5% 7,85 g/100g). The cocona and the breads added with its flour were classified as foods of low glycemic index and glycemic load, even with the addition of the flour in small concentrations (2,5% and 5%). Considering the sensorial analysis of the breads added with the fruit flour, the PI 2,5% was the one that obtained the best acceptance. The obtained results demonstrate that breads with minimal concentrations of cocona (2,5%) can be associated to the alimentary consumption of diabetic individuals, favoring their glycemic control other complementary studies are necessary to evaluate the microbiological characteristics of the finished breads to conclude the safety of its conservation status, as well as its interaction with the glycemic profile of individuals with Diabetes mellitus.